Constraining sulphur yields of trachytic and phonolitic volcanic eruptions: Tambora, Vesuvius, Laacher See and Campi Flegrei - Scaillet, Bruno; Oppenheimer, Clive; Cioni, Raffaello; Scaillet, Stephane; Moussallam, Yves; Prouteau, Gaelle; Andújar, Joan (Comptes Rendus. Géoscience, 2024)
International audience Evolved alkaline magmas have fuelled renowned large explosive eruptions, including that of Tambora in 1815. Very high sulphur yields to the atmosphere have been suggested for some prominent phonolite-trachyte eruptions, influencing assessments of their potential climatic impacts. However, the implications of alkalinity on volatile abundances in melts remain only partially understood. Here, we draw on available petrological and thermodynamical constraints, accounting for uncertainty in pre-eruptive magma redox state, to quantify pre-eruptive sulphur budgets for several prominent phonolite-trachyte eruptions. We thereby calculate upper limits for suphur yields for the 13 kyr calBP Laacher See eruption (3-15 Tg S), the plinian component of the 39.85 ka Campanian Ignimbrite (2-9 Tg S), and the 1890 calBCE "Avellino" and 79 CE eruptions of Vesuvius. Our findings demonstrate that alkali-rich magmas do not outstrip dacite or rhyolite arc compositions in respect of sulphur abundance and can inform both climate modelling efforts and the search for the eruptions' signatures in ice core records.